Damaging micromechanisms characterization in a ferritic-pearlitic ductile cast iron (Fracture and Structural Integrity, 2014)
The analysis of the damaging micromechanisms in Ductile Cast Irons is often focused on ferritic matrix. Up to ten years ago, for this grades of DCIs, the main damaging micromechanism was identified with the graphite elements – ferritic matrix debonding. More recent experimental results showed the presence of an internal gradient of mechanical properties in the graphite elements and the importance of other damaging micromechanisms, with a negligible importance of the graphite elements – ferritic matrix debonding mechanism. In this work, damaging micromechanisms development in a ferritic – pearlitic DCI have been investigated by means of tensile tests performed on mini-tensile specimens and observing the specimens lateral surfaces by means of a scanning electro microscope (SEM) during the tests (“in-situ” tests). Experimental results have been compared with the damaging micromechanisms observed in fully ferritic and fully pearlitic DCIs
Keywords: Ductile Cast Irons